ANALISIS MASLAHAH: PASAR MODAL SYARIAH SEBAGAI INSTRUMEN INVESTASI DI INDONESIA - Yenni Batubara (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2020)
The Capital Market is one of the investment instruments that is of interest to the public. The development of the capital market in Indonesia is not only developing conventionally, but also in sharia. Investing in the capital market in Indonesia is supported by people who in fact are Muslim towards investment instruments that comply with sharia principles. The capital market drives significant capital market growth. This study aims to look at the benefit of the capital market with normative research methods, and with descriptive data analysis techniques. From the results of the analysis conducted, it can be concluded that doing economic benefit by providing the capital market as an investment instrument in Indonesia can handle speculative practices and other practices that are not in accordance with sharia principles in capital market operations. The affirmation of the rule of law governing transactions in the capital market also fosters the Islamic capital market. For economic goals that are implemented, the benefits for the emite and investors. In addition to the benefits of the parties to the transaction, this will also encourage economic growth in accordance with the growth of the Islamic capital market in Indonesia.